1985
DOI: 10.1055/s-2007-1014143
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Angiographie Late Results Following Enlargement of Narrow Aortic Root Using Autologous Pericardium in Prosthetic Aortic Valve Replacement

Abstract: From 1976 to 1984, 31 patients underwent enlargement of very small aortic roots using autologous pericardial strips the subannular part of which extended into the incised anterior mitral valve leaflet. The majority of these interventions (n = 24) were carried out before the end of 1980. Over an average follow-up period of 52.5 months, only one of the surviving patients had a complication traceable to the pericardial implantation (aneurysmatic patch dilatation), and 2 late deaths were also not directly connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…An AV patient–prosthesis mismatch with first generation prosthetic heart valves were more common than new generations of prosthetic heart valves with greater effective orifice area, but it may still perform aortoplasty to prevent patient–prosthesis mismatch. One of the most used aortoplasty surgeries is the Manouguian procedure [4]. Using pericardial patch in this procedure has become more common which has been associated with more late complications, such as patch aneurysm, aortic dissection, paraaortic leakage, MV insufficiency [4], and endocarditis [3], [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An AV patient–prosthesis mismatch with first generation prosthetic heart valves were more common than new generations of prosthetic heart valves with greater effective orifice area, but it may still perform aortoplasty to prevent patient–prosthesis mismatch. One of the most used aortoplasty surgeries is the Manouguian procedure [4]. Using pericardial patch in this procedure has become more common which has been associated with more late complications, such as patch aneurysm, aortic dissection, paraaortic leakage, MV insufficiency [4], and endocarditis [3], [4].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most used aortoplasty surgeries is the Manouguian procedure [4]. Using pericardial patch in this procedure has become more common which has been associated with more late complications, such as patch aneurysm, aortic dissection, paraaortic leakage, MV insufficiency [4], and endocarditis [3], [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mirsadraee et al [35] was able to show significantly lower calcium levels in fresh/frozen pericardia compared with glutaraldehyde-fixed pericardia, 117 mg/g versus 332 μg/g Ca 2+ , respectively, of tissue dry weight (p<0.001). Other studies showed the fate of using autogenic pericardia, even in the systemic circulation [36,37]. …”
Section: Discussionmentioning
confidence: 99%